POLITIK HUKUM OTONOMI KHUSUS BERDASARKAN UNDANG UNDANG NOMOR 11 TAHUN 2006 TENTANG PEMERINTAHAN ACEH - Jefrie Maulana (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
Special autonomy needs to be examined further on the constitution in terms of providing loopholes or justifying the implementation of special autonomy, so that harmonization and synchronization of statutory regulations can be realized. The purpose of this study is to analyze the formation of the Law on Aceh Government in accordance with the mandate of the constitution and to determine the juridical consequences of the enactment of the Law on Governing Aceh. The results showed that the Special Autonomy of Aceh Province is a mandate of the constitution as viewed from the historical approach to the constitution regarding regional governance. The juridical consequence in terms of Indonesian constitutionality is that Aceh as a regional government has broad authority in the administration of autonomy with the broadest possible principle of special autonomy. Keywords: legal policy, special autonomy, government, Aceh